Inclusion of older patients with cancer in randomised controlled trials with patient-reported outcomes: a systematic review. Issue 4 (12th November 2019) - Sparano, Francesco; Aaronson, Neil K; Sprangers, Mirjam A G; Fayers, Peter; Pusic, Andrea; Kieffer, Jacobien M; Cottone, Francesco; Rees, Jonathan; Pezold, Mike; Anota, Amelie; Charton, Emilie; Vignetti, Marco; et al.
Abstract : Objectives: Inclusion of patient-reported outcomes (PROs) in cancer randomised controlled trials (RCTs) may be particularly important for older patients. The objectives of this systematic review were to quantify the frequency with which older patients are included in RCTs with PROs and to evaluate the quality of PRO reporting in those trials. Methods: All RCTs with PRO endpoints, published between January 2004 and February 2019, which included a patient sample with a mean/median age ≥70 years, were considered for this systematic review. The following cancer malignancies were considered: breast, colorectal, lung, prostate, gynaecological and bladder cancer. Quality of PRO reporting was evaluated using the International Society for Quality of Life Research–PRO standards. Studies meeting at least two-thirds of these criteria were considered to have high-quality PRO reporting. Results: Of 649 RCTs identified with a PRO endpoint, only 72 (11.1%) included older patients. Of these, 35 trials (48.6%) were conducted in patients with metastatic/advanced disease. PROs were primary endpoints in 20 RCTs (27.8%). Overall survival was the most frequently reported clinical outcome in studies of patients with metastatic/advanced cancer (n=28, 80%). One-third of the RCTs (n=24, 33.3%) were considered to have high-quality PRO reporting. Overall, the largest prevalence of RCTs with high-quality PRO reporting was observed in prostate and colorectal cancers. Conclusions: Our review indicates not only that PRO–RCT-based studies in oncology rarely include older patients but also that completeness of PRO reporting of many of them is often suboptimal.